On the design of a fractal calibration pattern for improved camera calibration - Schilling, Hendrik; Diebold, Maximilian; Gutsche, Marcel; Jähne, Bernd (Technisches Messen, 2017)
Camera calibration, crucial for computer vision tasks, often relies on planar calibration targets to calibrate the camera parameters. This work describes the design of a planar, fractal, self-identifying calibration pattern, which provides a high density of calibration points for a large range of magnification factors. An evaluation on ground truth data shows that the target provides very high accuracy over a wide range of conditions.
Gesehen am 07.05.2018